Characteristic Of A Mother Pregnant In The COVID-19 Pandemic - Fatimah Fatimah; Prasetya Lestari; Lia Dian Ayuningrum (Alma Ata University Press, 2020)
Coronavirus disease is a viral disease of a new spesies have never identified earlier in humas. A disease that can be causing misery of difficulties in acces to helth services. An increase in Indonesia so quickly that pregnant women get the very limited in degree standards of service for reduse for pandemics. Seering this condition for interested researchers know characteristic of pregnant women in the pandemic. Research objectives know characteristic of a mother pregnant in the pandemic. Research methodology for 3 rd trimester of pregnant women in Yogyakarta. Many sample was 32 the 3 rd trimester women. The research results in terns of education and higer education is senior high school as many as 21 (65,6%), while in collage as many as 9 (28,1%) and primary school 2 (6,3%). Capital work pregnant most mother with as a housewife one as many as 22 people (68,8%), employees as many as 7 people (21,8%). The other with traders, work teachers and public servants. And in term of pregnancy more primigravida or pregnancy first and the 18 people (56,3%), the second one as many as 11 people (34,5%), the third child one as many as 2 people (6,3%), and fourth son ane as many as1 people (3,1%). Conclusion based on work as a housewife, education is senior high school and more on the pregnant priigravida or anew first.